How to convert this for loop to parfor loop?

1 回表示 (過去 30 日間)
Ahmad Gad
Ahmad Gad 2017 年 11 月 8 日
編集済み: Ahmad Gad 2017 年 11 月 8 日
Hello All, I am very new to parallel computing, and I am having hard time converting all my for loops to parfor loops. However, If I understood how to convert this part, I think I will be able to convert many parts of my code. Any help will be appreciated.
I = size(A,1);
J = size(B,2);
parfor i = 1:I
for j = 1:J
C(i,6*j - 5) = U(6*B(i,j) - 5,1);
C(i,6*j - 4) = U(6*B(i,j) - 4,1);
C(i,6*j - 3) = U(6*B(i,j) - 3,1);
C(i,6*j - 2) = U(6*B(i,j) - 2,1);
C(i,6*j - 1) = U(6*B(i,j) - 1,1);
C(i,6*j - 0) = U(6*B(i,j) - 0,1);
end
end

回答 (0 件)

カテゴリ

Help Center および File ExchangeRandom Number Generation についてさらに検索

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by